Higher risk of vitamin D insufficiency/deficiency for rural than urban dwellers. Issue 197 (March 2020) - Griffin, Tomás P; Wall, Deirdre; Blake, Liam; G Griffin, Damian; Robinson, Stephanie; Bell, Marcia; Mulkerrin, Eamon C; O'Shea, Paula M
Highlights: Vitamin D deficiency is a major global health problem. Serum 25(OH)D was lower among rural v. urban dwellers irrespective of season. Vitamin D deficiency was greater in rural v. urban dwellers in spring, autumn and winter. Serum 25(OH)D was higher and the prevalence of deficiency lower in females v. males. Vitamin D deficiency was most prevalent among those age ≥80 years and ≤39 years. Abstract: There are many risk factors for Vitamin D deficiency. This study aimed to compare the Vitamin D status and serum 25(OH)D concentrations of adults living in an urban area to adults living in a rural area in the West of Ireland (latitude 53.27° North). A cross-sectional retrospective analysis of clinical records was performed. Following interrogation of the electronic laboratory information system, individuals who had serum 25(OH)D concentrations measured at Galway University Hospitals between January 2011 and December 2015 were identified. Clinical demographics, setting and date of sampling were recorded. In total, 17, 590 patients (urban n = 4, 824; rural n = 12, 766) were eligible for inclusion. Serum 25(OH)D concentrations were lower among rural compared to urban dwellers irrespective of season (spring p < 0.001, summer p = 0.009, autumn p = 0.002, winter p < 0.001). There was a significant difference in Vitamin D status between urban and rural dwellers in three of the four seasons: spring- deficiency: 16%-v-23%, insufficiency: 39%-v-43%, sufficiency: 45%-v-35% (p < 0.001); autumn- deficiency: 11%-v-10%, insufficiency: 30%-v-35%, sufficiency: 59%-v-56% (p = 0.01); winter- deficiency: 23%-v-25%, insufficiency: 35%-v-42%, sufficiency: 41%-v-33% (p < 0.001). Serum 25(OH)D concentrations were higher and the prevalence of deficiency lower in urban/rural females compared to urban/rural males (p < 0.001). Serum 25(OH)D concentrations increased sequentially from the 18−39 year age group to the 60−69 year age group in both urban (p < 0.001) and rural (p < 0.001) dwellers and then decreased progressively as age increased to ≥90 years. The odds of Vitamin D deficiency increased with age, lower daily sunshine hours, male gender, rural address and season.